Respostas

A melhor resposta!
2014-07-01T16:05:31-03:00
r = a2 - a1
r = (x + 2)² - x² 
r = x² + 4x + 4 - x² 
r = 4x + 4 

r = a3 - a2 
r = (x + 3)²- (x + 2)² 
r = x² + 6x + 9 - (x² + 4x + 4) 
r = x² + 6x + 9 - x² - 4x - 4 
r = 2x + 5 

Logo: 
4x + 4 = 2x + 5 
2x = 1 
x = 1/2
1 5 1
2014-07-01T16:12:48-03:00
P.a. (x+2)²-x² = (x+3)²-(x+2)² <--> 
2·(x+2)²= x²+(x+3)² <--> 
2x²+8x+8= 2x²+6x+9 <--> 
2x= 1 <-> 
x=1/2 

==> P.a. { 1/4, 25/4, 49/4}
1 5 1
a1 = x²

a2 = (x+2)²

a3 = (x+3)²



(x+2)² - x² = (x+3)² - (x+2)²

x²+4x+4 - x² = x²+6x+9 - (x²+4x+4)

x²+4x+4 - x² = x²+6x+9-x²-4x-4

4x+4 = 6x-4x+9-4

4x-6x+4x = 9-4-4

8x-6x = 5-4

2x = 1

x = 1/2